Topical retinol attenuates stress‐induced ageing signs in human skin ex vivo, throughEGFR activation viaEGF, but notERK andAP‐1 activation - Romana‐Souza, Bruna; Silva‐Xavier, Welker; Monte‐Alto‐Costa, Andréa (Experimental dermatology, 2019)
Stress‐induced oxidative damage and the inflammatory response lead to degradation of collagen and elastic fibres and wrinkle formation. Topical retinol (or vitamin A) can be a strategy to attenuate the effects of stress in skin as it promotes collagen and elastic fibre production and reduces protease synthesis. This study investigated the effect of topical retinol in stressed human skin using in vitro and ex vivo models. Human skin explants were treated with high levels of epinephrine (as observed in stressed patients) and topically with retinol for 13 days. Human dermal fibroblasts were treated with conditioned medium of ex vivo retinol‐treated and non‐stressed (without epinephrine) human skin for 24 hours. In ex vivo human skin, retinol reversed the epinephrine‐induced reduction in epidermal proliferation and differentiation, normalizing epidermal thickness. Retinol also inhibited the epinephrine‐induced reduction in elastic fibre deposition and organization, restoring dermal thickness. In addition, retinol reversed the epinephrine‐induced increase in c‐JUN protein expression, but it did not alter extracellular signal‐regulated kinase 1/2 (ERK) phosphorylation in ex vivo human skin. Conditioned medium of ex vivo retinol‐treated and non‐stressed human skin presented an increased protein expression of epidermal growth factor (EGF). In human dermal fibroblasts, conditioned medium of ex vivo retinol‐treated and non‐stressed human skin increased protein and gene expression of fibrillin‐1 and protein expression of EGF receptor (EGFR). In conclusion, topical retinol attenuates stress‐induced skin ageing signs in human skin ex vivo, probably through EGFR activation via EGF, but not by the stress‐activated ERK 1/2 and c‐JUN pathways.